2022
DOI: 10.1007/s10896-022-00381-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Domestic Violence Housing First Model on Survivors’ Safety and Housing Stability: Six Month Findings

Abstract: Intimate partner violence (IPV) is a leading cause of homelessness, yet little evidence exists about effective strategies to assist IPV survivors as they work to avoid homelessness while freeing themselves from abuse. An ongoing demonstration evaluation is examining if and how one promising model assists IPV survivors in obtaining safe and stable housing over time. The Domestic Violence Housing First (DVHF) model involves providing IPV survivors with mobile advocacy and/or flexible funding, depending on indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These participants may or may not have also received other agency services. After accounting for advocate and agency, logistic regressions confirmed that minority status was not a significant predictor of services received ( Sullivan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These participants may or may not have also received other agency services. After accounting for advocate and agency, logistic regressions confirmed that minority status was not a significant predictor of services received ( Sullivan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 98%
“…Thirty-six percent of the remaining participants were considered to have received SAU because they had received services but (1) had not received housing-focused advocacy, despite needing such help; and (2) had not received cash assistance. Survivors who had received housing-focused advocacy and/or cash assistance were categorized as having received DVHF (64%) (see Sullivan et al, 2022 for more detail). Eight participants who were not interviewed at the 6-month follow-up were regained into the study at the 12-month follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We intentionally chose a nonrandomized comparative effectiveness design for this study to capitalize on how services are provided in community settings . Due to staff turnover, fluctuation in agency resources, and other factors typical of nonprofit human service agencies, we knew that some survivors would receive DVHF while others would receive SAU, such as support groups, counseling, legal advocacy, and referrals . Written informed consent was obtained from participants before the start of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of the intervention is for survivors to achieve safe and stable housing and psychological well-being. In a longitudinal demonstration evaluation comparing survivors who received DVHF with those who received services as usual (SAU), the DVHF model was more effective than SAU in improving survivors’ housing stability, safety, and mental health over a period of 24 months (Sullivan et al, 2023). With growing evidence of the effectiveness of the DVHF model, it is now critical to examine the situational factors that impact the effectiveness of the intervention.…”
Section: Ipv Mental Health and Well-beingmentioning
confidence: 99%